Assessment of Radioactive Gaseous Effluent Released from Ninh Thuan 1 Nuclear Power Plant under Scenario of INES-level 7 Nuclear Accident - Khai, Nguyen Tuan; Cuong, Le Dinh (Communications in Physics, 2016)
<!– p margin-bottom: 0.1in; direction: ltr; line-height: 120%; text-align: left; widows: 2; orphans: 2; p.western p.cjk p.ctl font-family: "Calibri"; a:link color: rgb(0, 0, 255); –> Based on guidance RG 1.109, RG 1.111 published by United States Nuclear Regulatory Commission (USNRC) our research concentrates on assessing radiation doses caused by radioactive substances released from the Ninh Thuan 1 nuclear power plant (NPP) to the environment under scenario of an INES-level 7 nuclear accident caused by two incidents: Station Black Out (SBO) and Loss of Coolant Accident (LOCA) using software RASCAL4.3 provided by the Emergency Operations Center of USNRC. The NPP Ninh Thuan 1 is assumed to use the VVER-1200 technology with a total power of 2400 MWe from two units. The input data for the model calculations is built based on the accident scenario, the technical parameters of VVER-1200 technology and the meteorology. In this work the meteorological data on dry and rainy seasons which are typical for the Ninh Thuan region was considered. The maximum dose distributions were calculated within 40 km from the NPP site. The distributions are strongly affected by meteorological conditions. In the rainy season the dose values near the plant are higher than those in the dry season due to deposition effect of the radioactive substances. The calculation results show that consequences of the accident are very serious. A total radioactivity of radiological equivalence 225,000 TBq to 131I released to the atmosphere. Within 20km the Total Effective Dose Equivalence (TEDE) values are very high, about several tens of times greater than the dose limit. It is requested to establish National Steering Board for Accident Response to direct the relevant authorities in response for the accident consequences and ensure for security in the area of NPP. The public communication, emergency preparedness plan, people evacuation must be implemented under the guidance of Circular 25/2014/TT-BKHCN